Performance Analysis of the DCCHP Exhaust Waste Heat Coupled Air Source Heat Pump System - Yongsheng TAN (发电技术)
As an efficient way of energy utilization, the exhaust temperature after exhaust waste heat recovery of the internal combustion engine distributed combined cooling heating and power (DCCHP) systems is about 100℃, and some of the low temperature waste heat is still not fully utilized. To achieve the deep recovery of exhaust waste heat, a DCCHP dynamic exhaust low temperature waste heat coupled air source heat pump system was proposed in this paper. Based on the DCCHP system of 10 kW internal combustion engine, the effects of the recyclable waste heat of the system, the coefficient of performance (COP) of the heat pump and the impact of the primary energy utilization rate was studied. The results show that under the design condition, the exhaust waste heat of DCCHP system is 1.22 kW, the recyclable waste heat of heat pump system is up to 1.07 kW, the exhaust waste heat recovery rate is 87.7%, the COP is up to 4.66, increasing 39.5%. The primary energy utilization efficiency is increased by 3.9%. The problems of frosting and poor performance of heat pump evaporator unit in cold region were solved. This study provides an important reference for the combined and efficient application of CCHP systems and heat pump units.